2022
DOI: 10.1093/hmg/ddac043
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal endothelial and macrophage gene expression in atrophic and neovascular macular degeneration

Abstract: The human choroid is a heterogeneous, highly vascular connective tissue that dysfunctions in age-related macular degeneration (AMD). In this study, we performed single-cell RNA sequencing on twenty-one human choroids, eleven of which were derived from donors with early atrophic or neovascular AMD. Using this large donor cohort, we identified new gene expression signatures and immunohistochemically characterized discrete populations of resident macrophages, monocytes/inflammatory macrophages, and dendritic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 63 publications
1
55
0
Order By: Relevance
“…To the best of our knowledge, there are currently no other public datasets thatcontain more samples suitable for our analysis. For example, although a recent scRNA-seq dataset from Voigt et al (2022) contains more eye samples, it is not suitable for our intercellular communication study. Specifically, as cells have been sorted based on CD31 expression to enable the capture of endothelial cells, only a low number of RPE cells are present in the dataset and they are moreover confounded with photoreceptors (Voigt et al, 2019(Voigt et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are currently no other public datasets thatcontain more samples suitable for our analysis. For example, although a recent scRNA-seq dataset from Voigt et al (2022) contains more eye samples, it is not suitable for our intercellular communication study. Specifically, as cells have been sorted based on CD31 expression to enable the capture of endothelial cells, only a low number of RPE cells are present in the dataset and they are moreover confounded with photoreceptors (Voigt et al, 2019(Voigt et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“… EPOR mRNA expression in RPE/choroids from adult human donor eyes. EPO mRNA was detected in ( A ) macular and ( B ) extramacular RPE/choroids that were isolated from donors with AMD (red dots), including dry AMD (green dots) and wet AMD (purple dots), or without AMD (blue dots), and EPOR mRNA was detected in ( A ) macular or ( B ) extramacular RPE/choroids that were isolated from donors with AMD (black dots), including dry AMD (brown dots) and wet AMD (dark blue dots), or without AMD (orange dots) that were collected in a previous publication [ 26 ]; ( C ) EPOR mRNA was also detected in single cells dissociated from RPE/choroids from patients without AMD (green dots) or with dry AMD (red dots) or wet AMD (blue dots) that were collected in a previous publication [ 28 , 29 ]. …”
Section: Resultsmentioning
confidence: 99%
“…We found that EPOR mRNA is expressed in several cell types in RPE/choroids isolated from human donors, including macrophages and choriocapillaris endothelial cells using a publicly available database [ 29 ]. We previously observed that the RPE/choroids of mice with overactive EPOR signaling had more macrophages prior to laser-induced injury, greater concentrations of inflammatory cytokines three days after laser-induced injury, and increased laser-induced CNV seven days after laser-induced injury compared to littermate wildtype control mice [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations